Thermal change of amorphous indium tin oxide films sputter-deposited in water vapor atmosphere - M. H. Wang (2018)
Amorphous ITO thin films were deposited on silicon wafers at room temperature by RF + DC magnetron sputtering at water vapor partial pressures between 0 and 6 × 10- 5 Torr. The O/(In + Sn) ratio was determined by Rutherford backscattering spectroscopy. The effect of water vapor on the thermal crystallization process was monitored by high-temperature X-ray diffraction (XRD) analysis. We found a simple dependence between the crystallization temperature and the water vapor partial pressure. After the high-temperature XRD, the films deposited at low water vapor pressures (2 × 10- 5 Torr or lower) exhibited <100> preferred orientation, whereas those deposited at high water vapor pressures (3 × 10- 5 Torr or higher) exhibited <111> preferred orientation. Introduction of water vapor during the deposition decreased carrier concentration and increased mobility. The carrier concentration after thermal crystallization was dependent on the water vapor partial pressure. © 2007 Elsevier B.V. All rights reserved.